Overview of Research Activities on Deposit Formation in Diesel Engine Combustion Chamber - Ho, Thanh Tung; Pham, Van Viet; Hoang, Anh Tuan; Le, Anh Tuan (Old Journal, 2020)
The paper presents an overview of the deposit formation in diesel engine combustion chamber by clarifying the physical and chemical mechanisms of the deposit formation and the deposit removal, the factors affecting deposit formation by condensation, sticking, adsorption, chemical reaction mechanisms, and the factors influencing deposit removal by physical, mechanical and chemical mechanisms. The paper also analyses and evaluates deposit parameters and images obtained from a number of typical case studies to verify the deposit formation and removal mechanisms. Research findings are significant to suggest measures to minimize deposits in the diesel engine combustion chamber, contributing to enhancing the engine performance and engine durability.